Dampak Ekspansi Ritel Modern Terhadap Keberlangsungan UMKM di Kabupaten Dairi: Tantangan dan Strategi Dalam Perekonomian Indonesia - Daud Frandes Sianturi; Nadine Winata Silitonga; Joice Lwisa Nababan; Dian Sasmita Pasaribu (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2026)
The expansion of modern retail in Dairi Regency has raised concerns regarding the sustainability of local Micro, Small, and Medium Enterprises (MSMEs). This study aims to analyze the impact of this expansion on MSME performance and evaluate adaptive strategies that can be implemented. This research employs a literature study method by collecting secondary data from various sources, such as academic journals and government reports. The findings indicate that the expansion of modern retail can have negative impacts on the income of Micro, Small, and Medium Enterprises (MSMEs), a reduction in job opportunities, and a weakening of the local economy. However, by adopting adaptive strategies such as digital transformation, product quality improvement, and strategic collaboration, MSMEs can enhance their competitiveness. The implementation of supportive government policies also plays a crucial role in maintaining MSME sustainability amidst competition with modern retail